Contemporary online Indonesian folk literature for 21st century learners - Dwi Indra Aprilliandari (UAD TEFL International Conference)
This research intends to acknowledge the advantages of contemporary online Indonesian folk literature for 21st century learners. The 21st century is a technology era where information can be spread faster and an internet connection is the most important thing to share all the information around the world. It is qualitative research which are aimed at revealing the use of Indonesian folk literature for Indonesian learners which learn English as a foreign language. There is still a lack of research about Indonesian folk literature for 21st century learners; therefore, this research is significant to be conducted. The finding of this research can be described as follows: First, contemporary online Indonesian folk literature is as an instructional media that combine the positive sides of traditional mode such as define, extract and deliver the moral values contain in literary works with technology use to keep, improve and engage the students’ interest to learn English but reminds to keep their culture roots. Second, technology improves the learners to combine the traditional and modern ways of learning. Third, 21st century skills help the learners to be able to compete in this era.